2015
DOI: 10.1104/pp.15.01562
|View full text |Cite|
|
Sign up to set email alerts
|

A G-Box-Like Motif Is Necessary for Transcriptional Regulation by Circadian Pseudo-Response Regulators in Arabidopsis

Abstract: PSEUDO-RESPONSE REGULATORs (PRRs) play overlapping and distinct roles in maintaining circadian rhythms and regulating diverse biological processes, including the photoperiodic control of flowering, growth, and abiotic stress responses. PRRs act as transcriptional repressors and associate with chromatin via their conserved C-terminal CCT (CONSTANS, CONSTANS-like, and TIMING OF CAB EXPRESSION 1 [TOC1/PRR1]) domains by a still-poorly understood mechanism. Here, we identified genome-wide targets of PRR9 using chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 82 publications
4
134
0
3
Order By: Relevance
“…A number of potential regulatory cis-acting elements, including the LUX binding site (GATA/TGC) , TCP binding site (GGNCCCAC) (Pruneda-Paz et al, 2009), protein box (ATGGGCC) (Michael et al, 2008), and morning element (AACCACGAAAA) were absent, whereas a G-box (CACGTG) (Schindler et al, 1992), four EEs (AAAATATCT) (Harmer et al, 2000), and a CCA1 binding site (CBS; AACAATCT or AAAAATCT) (Wang et al, 1997) were found in the region between 21416 and the start codon of PRR5 ( Figure 1A). Genomic sequences that coimmunoprecipitate with PRRs in vivo are enriched for G-boxes Nakamichi et al, 2012;Liu et al, 2013;Liu et al, 2016), and the regulatory elements EE and CBS are directly recognized by RVEs/CCA1/LHY in vitro and by REV8 in vivo (Wang et al, 1997;Alabadí et al, 2001;Rawat et al, 2011), but previous work had left it unclear whether or not CCA1 and LHY associate with PRR5 upstream in vivo.…”
Section: Cca1 Associates With Prr5 Upstream Regions In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…A number of potential regulatory cis-acting elements, including the LUX binding site (GATA/TGC) , TCP binding site (GGNCCCAC) (Pruneda-Paz et al, 2009), protein box (ATGGGCC) (Michael et al, 2008), and morning element (AACCACGAAAA) were absent, whereas a G-box (CACGTG) (Schindler et al, 1992), four EEs (AAAATATCT) (Harmer et al, 2000), and a CCA1 binding site (CBS; AACAATCT or AAAAATCT) (Wang et al, 1997) were found in the region between 21416 and the start codon of PRR5 ( Figure 1A). Genomic sequences that coimmunoprecipitate with PRRs in vivo are enriched for G-boxes Nakamichi et al, 2012;Liu et al, 2013;Liu et al, 2016), and the regulatory elements EE and CBS are directly recognized by RVEs/CCA1/LHY in vitro and by REV8 in vivo (Wang et al, 1997;Alabadí et al, 2001;Rawat et al, 2011), but previous work had left it unclear whether or not CCA1 and LHY associate with PRR5 upstream in vivo.…”
Section: Cca1 Associates With Prr5 Upstream Regions In Vivomentioning
confidence: 99%
“…Chromatin immunoprecipitation followed by deep sequencing (ChIP-seq) analyses combined with transcriptomics experiments indicate that clock-associated PRR family proteins directly repress key TFs involved in photoperiodic flowering, hypocotyl elongation, and cold stress responses Nakamichi et al, 2012;Liu et al, 2013;Liu et al, 2016). Genome-wide gene expression analyses using a chemically induced gene expression system revealed the potential targets of RVE8 and TOC1 (Gendron et al, 2012;Hsu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutations in the genes encoding pseudoresponse regulators (PRR9, PRR7, and PRR5), which are key components of the circadian oscillator, result in the upregulated expression of DREB1s and their downstream genes (Nakamichi et al, 2009(Nakamichi et al, , 2012. These three PRRs and a homolog, TIMING OF CAB EXPRESSION1, repress the expression of CIRCADIAN CLOCK ASSOCIATED1 (CCA1) and LATE ELONGATED HYPOCOTYL (LHY), generating a negative feedback loop for clock function (Nakamichi et al, 2009;Nagel et al, 2015;Kamioka et al, 2016;Liu et al, 2016). CCA1, which encodes a morning-expressed MYB transcription factor, can bind to the promoter regions of DREB1s, and cold-inducible expression of DREB1s has been reported to be significantly reduced in cca1 lhy double mutant plants (Dong et al, 2011), suggesting that CCA1 and its close homolog, LHY, are also important transcriptional activators in the cold-responsive expression of DREB1s.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in the NF-CO mutagenesis experiments of Figure 2, a C or a T at this position are essentially equivalent. Finally, the CCACGTG motif, resembling a G-box, and previously described in TOC1 and PRR chromatin immunoprecipitation (ChIP)-seq experiments and in promoters of genes upregulated after TOC1 overexpression (Gendron et al, 2012;Liu et al, 2016), was recovered from the nf-yc3 nf-yc4 nf-yc9 cohort and was the most enriched element in intersections involving this cohort. Collectively, these elements all contain or closely resemble the CCACA core motif identified by in vitro EMSAs as optimal for NF-CO.…”
Section: Nf-co Binds the Core Pentamer Ccaca With Preferred Flankingmentioning
confidence: 99%